GLONASS: Theory background and state of the art - Jerez, Gabriel Oliveira (2018)
GPS (Global Positioning System) and GLONASS (GLObal NAvigation Satellite System) development began in the seventies. They are currently the main GNSS (Global Navigation Satellite Systems) systems with full constellation available. Although both systems have achieved full constellation in near periods, GLONASS passed thru a fast degradation, mainly caused by the lack of investment and the non-launch of new satellites to replace the old and damaged ones. In this context the use of GPS/GLONASS combined data became not feasible in the late nineties caused by the GLONASS instability. However, in 2001 a modernization and restoration plan began and, since 2011, GLONASS have full constellation of 24 satellites with global coverage. With this new scenario, other studies become necessary. In this context this paper intended to review the main concepts related to the system, present a brief historic, structure and the modernization plan as well as some future perspectives.